The Role of Refund Expectations in Savings: Evidence from Volunteer Income Tax Preparation Programs in the United States. Issue 1 (22nd August 2016) - Porto, Nilton; Collins, J. Michael
Abstract : Millions of households in the United States receive federal income tax refunds annually, many for substantial amounts. Consumers can use the proceeds of income tax refunds for spending and saving, but tests of prior programs to encourage savings show low take‐up rates. This field study shows that the majority of tax filers make no estimate of their refund amount in advance, but that consumers who are able to estimate their refund in advance of completing their tax returns tend to be reasonably accurate in their estimates. Moreover, taxpayers who estimate their refunds before filing their taxes are more likely to save their refunds than those who do not. These results highlight the importance of expectations and planning with respect to savings decisions.